Umbelliferone protects testes and spermatogenesis against lead acetate by effectively mitigating oxidative stress, inflammation, and apoptosis - Maryam Hejazi; Roghaye Farajpoor Javazmi; Seyyed Majid Bagheri (Clinical and Experimental Reproductive Medicine, 2026)
Objective: Lead acetate exposure induces male reproductive toxicity through oxidative stress and inflammation, impairing spermatogenesis and testosterone production. Umbelliferone (UMB), a coumarin derivative with antioxidant and anti-inflammatory properties, may counteract these adverse effects. This study evaluated the protective effects of UMB on lead acetate-induced testicular toxicity in male Wistar rats, with a focus on sperm parameters, antioxidant status, inflammatory markers, and testicular histology.Methods: Thirty-two male Wistar rats were assigned to four groups (n=8 each): control (saline), lead (50 mg/kg lead acetate [intraperitonea]), lead+UMB (25 mg/kg), and lead+UMB (50 mg/kg). Treatments were administered daily for 21 days. Sperm parameters (count, motility, viability, morphology) were assessed, alongside measurements of antioxidant enzyme levels (superoxide dismutase, catalase, glutathione), malondialdehyde (MDA), serum testosterone, and mRNA expression of tumor necrosis factor-α, interleukin-6 (IL-6), transforming growth factor-β, IL-10, Bcl-2-associated X protein (Bax), and B-cell lymphoma-2 (Bcl-2). Testicular histology was evaluated using hematoxylin and eosin staining.Results: Lead exposure significantly reduced sperm quality, antioxidant enzyme levels, testosterone, and Bcl-2 expression, while increasing MDA, pro-inflammatory cytokines, and Bax expression (p